Pilot study on deploying a wireless sensor-based virtual-key access and lock system for home and industrial frontiers - Eboka, Andrew Okonji; Aghware, Fidelis Obukohwo; Okpor, Margaret Dumebi; Odiakaose, Christopher Chukufunaya; Okpako, Ejaita Abugor; Ojugo, Arnold Adimabua; Ako, Rita Erhovwo; Binitie, Amaka Patience; Onyemenem, Innocent Sunny; Ejeh, Patrick Ogholuwarami; Geteloma, Victor Ochuko (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
The rise in data processing activities vis-à-vis the consequent rise in adoption and adaptation of information and communication tech related approaches to resolve societal challenges has become both critical and imperative. Virtualization have become the order of the day to bridge various lapses of human mundane tasks and endeavors. Its positive impacts on society cannot be underestimated. This study advances a virtual wireless sensor-based key-card access system with cost-effective solution to manage access to restricted areas within a facility. We seek to integrate virtual key card access, web-access control, solenoid lock integration, and ESP32- controller to create a dependable internet of things (IoT)-enabled access control system. Results show system benefit includes improved security, improved convenience, privacy, efficiency with real-time control capabilities that will allows building administrators to track and manage access to the facility remotely.